tapping into artificial intelligence: Advanced technology to prevent crime and support reentry. - Martin, Eric; Moore, Angela (Corrections Today)
The article explores the potential application and benefits of artificial intelligence in crime prevention and offenders' participation with reentry programming. Topics covered include the challenge faced by community supervision officers in managing caseloads, the advantages of using advanced machine learning algorithms in detecting trends, and research and development projects funded by the National Institute of Justice.